Electrodeposition preparation of NiCo2S4 nanoparticles on a N-doped activated carbon modified graphene film for asymmetric all-solid-state supercapacitors. (14th June 2022) - Cui, Linlin; Xu, Hanping; An, Yingrui; Xu, Mincai; Lei, Zijie; Jin, Xiaojuan
Abstract : The active conductive material NiCo2 S4 was electrodeposited on the activated carbon-modified graphene flexible substrate to fabricate flexible electrodes for supercapacitors. Abstract : In this work, NiCo2 S4 nanoparticles were anchored on the surface of nitrogen doped activated carbon modified graphene (GNAC) by simple electrodeposition to prepare GNAC/NiCo2 S4 -15 composite electrode materials for high-performance supercapacitors. The insertion of nitrogen-doped activated carbon between graphene sheets effectively prevented the self-accumulation of graphene layers and provided a large number of active sites for a uniform growth of NiCo2 S4 nanoparticles. Due to the synergistic effect between NiCo2 S4 and graphene nanosheets, the GNAC/NiCo2 S4 -15 electrode showed a high specific capacitance (1495 mF cm −2 at a current density of 1 mA cm −2 ) and excellent cycling performance (the area ratio capacitance retained 88% after 3000 cycles). In addition, an asymmetric supercapacitor (ASC) was assembled with GNAC/NiCo2 S4 -15 and GNAC as positive and negative electrodes, respectively. At a power density of 3.834 mW cm −3, the prepared ASC provides a significant energy density of 0.613 mW h cm −3, which offers great prospects for the application of supercapacitors.